Komunikasi Rohani dan Realistis: Model-Model Komunikasi dalam Keluarga Kristiani - Pratama, Dominius Kristian (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2021)
Communication is a necessity for everyone. Christian families also need ways of communication to be practiced in the small community. Husband and wife, parents and children, are the parties directly involved in family communication. However, family members may tend to ignore problems in the daily activities of the family, while each member has a responsibility to solve them by means of appropriate communication. Family members need to work together to build communication that is appropriate for their respective situations. Communication can be seen as an art learned by the families in good times, but also a practical way to face trouble. This article proposes three models, that is, realistic, spiritual, and imaginative communication models that may inspire families to practice communication in the light of Christian spirituality. These models invite family members to speak more honestly, recommend particular topics to fill their conversations by bringing up the spiritual aspect, and relate their personal hopes with God’s will. Through the models of communication, family members can practice spiritual and realistic communication in their small Christian community and together experience growth in their life of faith.